Synthesis and Characterization of Soy-Based Polyurethane Foam with Utilization of Ethylene Glycol in Polyol - Firdaus, Flora Elvistia (Makara Journal of Technology, 2014)
The use of vegetable oils on replacing petroleum has attracted attention of many researchers. The chemical structure of vegetable oils are different from petrochemicals, so the structure of soybean oil has to be chemically modified through its unsaturated fatty acid chain in triglyceride. A two step process was conducted for the preparation of soy-polyol in designated temperatures; 50 °C, 60 °C, and 70 °C. Ethylene glycol (EG) as co-reagent was taking part in soy-polyol synthesis, and the soy-polyol was used as a sole polyol for polyurethane synthesis. Referred to the previous study, the existence of EG in polyurethane synthesis can improved physical properties of polyurethane foam. The aim of this research is using soy-derived polyol for petro-polyol replacement aligned with drop-off of petro-derived reagent; EG. One step process was applied for the foam synthesis. The ingredients for foam synthesis; soy-polyol, Toluene diisocyanate (TDI): a mixture of 2.4 and 2.6 isomers in ratio of 80:20 (TDI T-80), surfactant, and distilled water. The synergize of stoichiometry ratio of co-reagent EG to soy-epoxide with best temperature, with the absence of EG in polyurethane formula can produce an ultimate property of polyurethane foam.